Molecular Characterization of Carbapenem Resistant Gram?Negative Bacilli in a Tertiary Care Cancer Centre - Parthiban Rudrapathy; Shythya K; Sajani Samuel; Sarath KE; Saravanan Murugesan (International Journal of Pharma and Bio Sciences, 2022)
Infections are common in patients living with cancer, and they depend upon proper and effective antibiotics to both prevent and treat bacterial infections. Carbapenems are the drug of choice for the treatment of many multidrug resistant (MDR) hospital acquired infections. Resistance to carbapenems is also not uncommon and is increasingly being reported nowadays. The aim of this study was todetermine the prevalence of carbapenem resistant gram negative bacteria and its encoding genes from cancer patients at a tertiary care cancer centre in North Kerala, India. A total of 350 clinical samples were processed and analyzed during the study period. Among the samples processed GNB was the predominant (n = 140), followed by Gram-positive bacteria (n = 133) and fungi (n = 9). Much of the bacterial growth was observed in the age group 61-70. Urine samples were the predominant followed by blood. The most common isolate was Escherichia coli followed by Klebsiella pneumoniae.K. pneumoniae was highly resistant to all of the antibiotic groups when compared to E. coli. When compared to P. aeruginosa, A. baumannii showed high levels of resistance. Carbapenem resistance was found in 46 (32.8%) of the isolates. NDM-1 was the most predominant gene. Amikacin and colistin were found to be the most effective antibiotics tested. This study provides important data regarding prevalence of carbapenem resistance GNB and most importantly the current prevalence of NDM -1 and OXA-48, and the rising trend of NDM -1 in our tertiary care cancer centre.